2022
DOI: 10.3390/children9050695
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic Therapy for Treatment of Disease in Children—A Review of the Literature

Abstract: Photodynamic therapy is a mode of treatment whereby local irradiation of an administered photosensitizer with light of a specific wavelength generates cytotoxic reactive oxygen species. Despite the upward trend in the popularity of this method in adults, it is not yet commonly used in the treatment of children. Due to certain limitations, underdeveloped treatment regimens and potential side effects, the use of photodynamic therapy in the pediatric population is still in the initial phases of evaluation in clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 82 publications
0
5
0
Order By: Relevance
“…35 A 2022 systematic review of 81 studies found that PDT was a safe and effective treatment for various cutaneous and non-cutaneous diseases in the pediatric population. 36 Valladares et al's prospective trial reported complete remission of HS with PDT in 29/38 adult patients. 37 However, a recent systematic review found that most studies examining the use of standard PDT protocols in HS are of poor quality and carry a high risk of bias.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…35 A 2022 systematic review of 81 studies found that PDT was a safe and effective treatment for various cutaneous and non-cutaneous diseases in the pediatric population. 36 Valladares et al's prospective trial reported complete remission of HS with PDT in 29/38 adult patients. 37 However, a recent systematic review found that most studies examining the use of standard PDT protocols in HS are of poor quality and carry a high risk of bias.…”
Section: Discussionmentioning
confidence: 99%
“…In PDT, a photosensitizing substance such as aminolevulinic acid is used concomitantly with a light source to create reactive oxygen species which may result in cell death and the eradication of bacterial biofilms 35 . A 2022 systematic review of 81 studies found that PDT was a safe and effective treatment for various cutaneous and non‐cutaneous diseases in the pediatric population 36 . Valladares et al's prospective trial reported complete remission of HS with PDT in 29/38 adult patients 37 .…”
Section: Discussionmentioning
confidence: 99%
“…The selection and use of non-toxic PSs, concentration of the PS, and light dosage limit its use in children. Photosensitizers administered intravenously can be very uncomfortable in young patients [176].…”
Section: Limitations Of Apdt In the Clinicsmentioning
confidence: 99%
“…The challenge to find DNA binding molecules that do not interfere with the functions of normal cells and/or to overcome multidrug resistance to chemotherapeutics is the most desirable goal. In this direction, due to the high spatial and temporal control, photochemotherapy [22][23][24] and photodynamic therapy [25][26][27][28] allow the minimally invasive treatment of several kinds of cancer and other nonmalignant diseases. Such impressive selectivity is due to the role of light, which acts as a counterpart to small organic molecules that can be excited by the energy offered by light and affect the biological target.…”
Section: Introductionmentioning
confidence: 99%